Comparison of the effects of pretreatment with Veramix sponge (medroxyprogesterone acetate) or CIDR (natural progesterone) in combination with an injection of estradiol-17 beta on ovarian activity, endocrine profiles, and embryo yields in cyclic ewes superovulated in the multiple-dose Folltropin-V (porcine FSH) regimen - Bartlewski, Pawel M.; Seaton, Patricia; Szpila, Patrycja; Oliveira, Maria E. F. [UNESP]; Murawski, Maciej; Schwarz, Tomasz; Kridli, Rami T.; Zieba, Dorota A. (Elsevier B.V., 2015)
Follicular wave status at the beginning of exogenous FSH administration is an important contributor to variability in superovulatory responses in ruminants. Studies in ewes have shown a decrease in the number of ovulations when superovulation is initiated in the presence of ostensibly ovulatory-sized ovarian follicles. Hormonal ablation of large antral follicles with the progestin-estradiol (E-2-17 beta) treatment significantly reduces this variability in superovulated anestrous ewes, but the effects of the treatment in cycling ewes have not yet been assessed. Sixteen Rideau Arcott x Polled Dorset ewes (November-December) received either medroxyprogesterone acetate (MAP)-releasing intravaginal sponges (60 mg) or controlled internal drug release (CIDR) devices (containing 300 mg of natural progesterone) for 14 days (Days 0-14), with a single intramuscular injection of 350 mu g of E-2-17 beta on Day 6. The superovulatory treatment consisted of six injections of porcine FSH (Folltropin-V) given twice daily, followed by a bolus GnRH injection (50 mu g intramuscular) on Day 15. There were no differences (P < 0.05) in the ovulatory responses and embryo yields between the two groups of ewes. In both subsets of animals, the next follicular wave emerged similar to 2.5 days after an E-2-17 beta injection (P > 0.05). A decline in maximum follicle size after an E-2-17 beta injection was more abrupt in CIDR- compared with MAP-treated animals, and the ewes pretreated with exogenous progesterone had significantly more 3-mm follicles at the start of the superovulatory treatment. The metabolic clearance rate of exogenous E-2-17 beta appeared to be greater in MAP-treated ewes, but circulating concentrations of porcine FSH failed to increase significantly after each Folltropin-V injection in CIDR-treated animals. The CIDR-treated ewes exceeded (P < 0.05) their MAP-treated counterparts in serum E-2-17 beta concentrations during superovulation. In spite of differences in antral follicle numbers and endocrine profiles between MAP- and CIDR-treated cyclic ewes receiving E-2-17 beta before ovarian superstimulation, there were no differences in superovulatory responses. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Sheep; Progestin; Estradiol; Superovulation; Antral follicle; Ultrasonography